Ribosomal protein S3 interacts with the NF‐κB inhibitor IκBα. Issue 5 (20th January 2014) - Stanborough, Tamsyn; Niederhauser, Johannes; Koch, Barbara; Bergler, Helmut; Pertschy, Brigitte
Abstract : Our results suggest that IκBα sequesters not only p65 but also RPS3 in the cytoplasm. This would ensure maintenance of an RPS3 pool for the NF‐κB pathway as well as equimolar release of RPS3 and p65 upon stimulation. Abstract : RPS3 interacts with the NF‐κB inhibitor IκBα in resting cells and in vitro. The ankyrin‐repeats of IκBα mediate the interaction with the RPS3 C‐domain. IκBα facilitates the formation of a cytoplasmic complex with RPS3 and p65.